2010
DOI: 10.4314/sajas.v39i1.61328
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and non-genetic factors affecting body weight in Tellicherry goats

Abstract: Data on 566 Tellicherry goats, recorded between 1988 and 2007 were used to study the effect of nongenetic factors on body weight and daily gain from birth to 12 months of age. The least-squares means for body weight at birth and at 12 months of age were 2.17 ± 0.03 and 18.78 ± 0.44 kg, respectively. The preand post-weaning average daily weight gains were 72.41 ± 1.68 and 37.46 ± 1.49 g, respectively, and the associated growth efficiencies were 3.11 ± 0.08 and 1.34 ± 0.05, respectively. Significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 1 publication
11
19
1
Order By: Relevance
“…The heritability estimates of birth and weaning weights were moderate in magnitude. The present findings were well within the range of those obtained in other breeds (Yadav et al, 2008, Thiruvenkadan et al, 2009, Mandal et al, 2013. However lower estimates were reported by Roy et al (2008) in Jamunapari, Snyman, (2012 in Angora and Singh et al(2013) in Jamunapari kids.…”
Section: Genetic and Phenotypic Parameters Estimatessupporting
confidence: 93%
See 1 more Smart Citation
“…The heritability estimates of birth and weaning weights were moderate in magnitude. The present findings were well within the range of those obtained in other breeds (Yadav et al, 2008, Thiruvenkadan et al, 2009, Mandal et al, 2013. However lower estimates were reported by Roy et al (2008) in Jamunapari, Snyman, (2012 in Angora and Singh et al(2013) in Jamunapari kids.…”
Section: Genetic and Phenotypic Parameters Estimatessupporting
confidence: 93%
“…Similarly, comparable estimates for WADG and PADG were obtained by Singh et al (2009) andPandey (2013) in Mehsana. However, slightly lower estimates were obtained by Thiruvenkadan et al (2009) in Tellichery and by Husain et al (1996) in Black Bengal goats. The year of birth of kids had highly significant (P < 0.01) effect on body weights at all the developmental stages, but there were no clear cut patterns of growth over the years (Fig.1).…”
Section: Resultsmentioning
confidence: 76%
“…The moderate estimates of genetic correlation between the two traits were in accordance with those findings, which reported that genetic correlations between birth weight and 6 months weight in Tellicherry goat kids were 0.378±0.417 [11]. Moderate genetic correlations between the two traits were also reported by many other workers in different goat breeds around the world [9,17,19,22].…”
Section: Birth Weight and Six Month Weightsupporting
confidence: 79%
“…The high estimates of genetic correlation between the two traits were also supported by the findings of different workers in different goat breeds around the world [6][7][8][9][10][11]. Shafiq & Sharif [6] reported that the genetic correlations between birth weight and weaning weight were 0.70±0.49 in Teddy goats, while significant genetic (0.69) correlations were also reported between birth weight and weaning weight by Hyder et al [7] in Teddy goats.…”
Section: Birth Weight and Weaning Weightsupporting
confidence: 52%
See 1 more Smart Citation